The properties of composite panel manufactured from oil palm fibres and plastics / Engku Zaharah Engku Zawawi, Rahmah Mohamed and Suhaimi Muhammed - Engku Zawawi, Engku Zaharah; Mohamed, Rahmah; Muhammed, Suhaimi (Universiti Teknologi MARA Cawangan Pahang, 2000)
The utilisation of agricultural fibres into useful plastics product has introduce new alternative materials to the plastics industry. The waste agricultural products obtain from jute, padi, palm and oil palm are some of the materials which can be used as fillers in polymer. Attempts have been made to incorporate oil palm fibre into thermoplastics and thermoset systems. In thermoplastic matrix, oil palm fibre ( OPF ) from frond parts was incorporated into Polypropylene/Nylon blend in different ratios and fibre length. Mechanical properties especially flexural and impact properties was found to improve slightly. Generally, higher composition and fibre length do affect its processing characteristics during moulding. In thermoset system, OPF in a fixed composition was incorporated into unsaturated or vinyl ester resin. Variation in fibre length affected the density and water absorption of the composite. Although the OPF-plastics composite was inferior in terms of flexural properties compared to the unreinforced and reinforced glass system, the oil palm fibre-plastics composite can be regarded as a potential material for future application provided proper modifications are made.